2007
DOI: 10.1215/s0012-7094-07-13636-6
|View full text |Cite
|
Sign up to set email alerts
|

Hecke correspondence, stable maps, and the Kirwan desingularization

Abstract: Abstract. We prove that the moduli space M0,0(N, 2) of stable maps of degree 2 to the moduli space N of rank 2 stable bundles of fixed determinant over a smooth projective curve of genus g has two irreducible components which intersect transversely. One of them is Kirwan's partial desingularization MX of the moduli space MX of rank 2 semistable bundles with determinant isomorphic to OX (y − x) for some y ∈ X. The other component is the partial desingularization of PHom(sl (2) ∨ , W)/ /P GL(2) for a vector bund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…Thus on the fiber of M , the second blow-up π 2 : X 2 //G → X 1 //G is the partial desingularization of the fiber P(H ⊗ sl 2 )//SL 2 . In [19,Theorem 4.1], it was shown that the partial resolution is isomorphic to the moduli space M 0,0 (PH, 2) of degree two stable maps to PH. Note that Z 2 acts trivially on the projectivized normal cone.…”
Section: Kirwan's Partial Desingularizationmentioning
confidence: 99%
“…Thus on the fiber of M , the second blow-up π 2 : X 2 //G → X 1 //G is the partial desingularization of the fiber P(H ⊗ sl 2 )//SL 2 . In [19,Theorem 4.1], it was shown that the partial resolution is isomorphic to the moduli space M 0,0 (PH, 2) of degree two stable maps to PH. Note that Z 2 acts trivially on the projectivized normal cone.…”
Section: Kirwan's Partial Desingularizationmentioning
confidence: 99%
“…Definition-Proposition 2.1. ( [16]) Let E be a rank two vector bundle on X and p ∈ X. Let E vp be the kernel of the surjective map…”
Section: Some Remarks About the Rational Map ψ : P G+1mentioning
confidence: 99%
“…Since deg(i) = 0, the closure l := i(l \ (l ∩ X)) in N is a smooth conic. By [16,Proposition 3.6], l should be a Hecke curve or a conic in PV M ∼ = P g−1 for some M ∈ Pic 0 (X). In the latter case, l ∩ X = r, l \ r ⊂ PV s L ∩ PV M for some M ∈ Pic 0 (X).…”
Section: Some Remarks About the Rational Map ψ : P G+1mentioning
confidence: 99%
See 2 more Smart Citations